Co-solvent effects on reaction rate and reaction equilibrium of an enzymatic peptide hydrolysis. Issue 16 (11th April 2018) - Wangler, A.; Canales, R.; Held, C.; Luong, T. Q.; Winter, R.; Zaitsau, D. H.; Verevkin, S. P.; Sadowski, G.
Abstract : This work presents an approach that expresses the Michaelis constant K aM and the equilibrium constant K th of an enzymatic peptide hydrolysis based on thermodynamic activities instead of concentrations. Abstract : This work presents an approach that expresses the Michaelis constant K aM and the equilibrium constant K th of an enzymatic peptide hydrolysis based on thermodynamic activities instead of concentrations. This provides K aM and K th values that are independent of any co-solvent. To this end, the hydrolysis reaction of N -succinyl-l -phenylalanine- p -nitroanilide catalysed by the enzyme α-chymotrypsin was studied in pure buffer and in the presence of the co-solvents dimethyl sulfoxide, trimethylamine- N -oxide, urea, and two salts. A strong influence of the co-solvents on the measured Michaelis constant ( K M ) and equilibrium constant (K x ) was observed, which was found to be caused by molecular interactions expressed as activity coefficients. Substrate and product activity coefficients were used to calculate the activity-based values K aM and K th for the co-solvent free reaction. Based on these constants, the co-solvent effect on K M and K x was predicted in almost quantitative agreement with the experimental data. The approach presented here does not only reveal the importance of understanding the thermodynamic non-ideality of reactions taking place in biological solutions and in many technological applications, it also provides a framework for interpreting and quantifying the multifaceted co-solvent effects on enzyme-catalysed reactions that are known and have been observed experimentally for a long time.